1981
DOI: 10.1029/ja086ia07p05590
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional interaction of interplanetary shock waves with the bow shock and magnetopause: A comparison of theory with ISEE observations

Abstract: The propagation of shock waves in the solar wind and their three‐dimensional interaction with the terrestrial bow shock, magnetosheath, and magnetopause is examined theoretically and compared with observations made by the ISEE spacecraft. First the formulae underlying the new position and orientation of the bow shock front after the interaction are given. Then magnetic field and plasma data from the ISEE 1, 2, and 3 spacecraft are compared with the theoretical estimates of the propagation time of the shock wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 20 publications
7
33
0
Order By: Relevance
“…This motion is a result of changes of magnetosheath parameters downstream of the IP shock. These observations are in an agreement with the predictions based on the RankineHugoniot conditions [Grib et al, 1979;Zhuang et al, 1981].…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…This motion is a result of changes of magnetosheath parameters downstream of the IP shock. These observations are in an agreement with the predictions based on the RankineHugoniot conditions [Grib et al, 1979;Zhuang et al, 1981].…”
Section: Resultssupporting
confidence: 81%
“…Using the Rankine-Hugoniot conditions, Dryer et al [1967], Ivanov [1964], Dryer [1973], Shen and Dryer [1972], and Grib et al [1979] have shown that the interaction of the IP shock with the bow shock (which is a fast reversed shock) creates three discontinuities: the fast reverse shock (the original bow shock), fast forward shock (the original IP shock) and a contact discontinuity between these shocks in a one-dimensional hydrodynamic case. A comparison between the 3-D MHD simulations and experimental observations was prepared by Zhuang et al [1981] and the authors concluded that all observed discontinuities moved with velocities corresponding to the Rankine-Hugoniot conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The transmitted shock wave delimiting the region of high Alfven Mach number is between X= -10 and -15 R E , and the bump marking the progression of the compression of the magnetospheric field has moved further tailward, to around X= -20 R E . The dynamics of the shock interaction with the bow shock-magnetopause system seen in the simulation are in agreement with theoretical models [e.g., Grib et al, 1979;Zhuang et al, 1981] and observa tions [Winterhalter et al, 1981]. A detailed analysis com paring our simulation results with those from analytical MHD models will be reported elsewhere.…”
Section: Magnetospheric Dynamicssupporting
confidence: 72%